The Australian continent : a geophysical synthesis - Kennett, B. L. N. (Brian Leslie Norman), 1948-; Blewett, R. S.; Chopping, Richard (ANU Press and Geoscience Australia, 2018)
"This synthesis of geophysical results for Australia is designed to provide an summary of the character of the Australian continent through the extensive information available at the continental scale. We present a broad range of geophysical attributes for the continent nation. We also endeavour to examine the relationships between different fields, and their relations to known resources. The work represents part of a continuing collaboration between the Research School of Earth Sciences at The Australian National University and Geoscience Australia, with the objective of bringing together all aspects of the structure of Australia in convenient forms. The results build on the extensive databases assembled at Geoscience Australia, particularly for potential fields, supplemented by the full range of seismological information mostly from The Australian National University. The book builds in part on the AuSREM project, sponsored by the AuScope infrastructure organisation, to develop a 3-D representation of seismological structure beneath the Australian region. The diverse and extensive geophysical datasets available for Australia in part reflect the poor outcrop of bedrock geology for this ancient weathered continent, and the economic importance of this geology to the Australian economy through its resource potential. Geophysics provides an important way to examine the structures that lie beneath the cover. This book is intended to make a contribution to the UNCOVER initiative, which has identified improved information on the subsurface as a prerequisite for extending exploration in Australia from regions of exposure into those with sedimentary cover."--Foreword